The role of environmental taxation in environmental policy - Nagy, Zoltán (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
In recent years the issue of sustainable development and environmental protection have become a central issue, because of the increasing pollution. The environmental policy applies different types of instruments in order to realize the goals of environmental protection and sustainable development. Although the scale of these instruments are wide, but as the experience shows the economic instruments are the most effective ones considering all of the adverse consequences. The environmental taxes have got more and more significance between the economic instruments. Their significance can be showed by their revenues. In the European Union’s regulation the supranational harmonisation of these instruments is inevitable, which is well represented by the regulation of energy taxation. Lots of barriers and counterarguments can be brought up against the environmental taxes, but a better instrument in the field of environmental regulation has not been invented yet.